Correlation between the Induction Program and the Performance of Early Childhood Beginner Teacher - Rahmat, Fauziah (Proceeding of International Conference on Teacher Training and Education, 2016)
This article discusses how the induction program correlates with the performance of an early childhood beginner teacher. The population in this research is early childhood education beginner teacher. That is, they that have the working experience less than or equal to three years ( Â month). While the sample in this study is taken with the non probability sampling techniques. The instrument used to collect the data is the questionnaire. The hypothesis in this study is there is a correlation between the induction program for beginner teacher and the performance of early childhood education beginner teacher. In this case the intended variables are the induction program for beginner teachers (x) and beginner teacher performance (y). The measurements are performed using Pearson product moment correlations because data from both a variable analyzed in the form of data interval. The result shows that there is no correlation between the induction program for beginner teacher and the performance of early childhood education beginner teacher (under the 0.05 criteria).